Bringing Digital Learning to Rural Schools: A Rapid Evaluation of Lyra in Africa - Simmons, Hannah (EdTech Hub, 2023)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Report of Case Studies on Responses to the Covid-19 Pandemic in Africa’s Educational Systems - Kiru, Elisheba; Ochieng, Vollan; Wawire, Brenda; Habiamana, Oliver; Ngware, Moses (APHRC, 2023)
This report presents case studies from seven African countries (i.e., Burkina Faso, Kenya, Malawi, Mali, Mozambique, Niger, and Nigeria) that implemented programs and innovations in response to the effects of the COVID-19 pandemic on the education systems. The report provides insights into building resilience within Africa’s education systems for the future. The case studies fill existing knowledge gaps on promising practices and add value to discussions on the contextual drivers that facilitated the implementation of the interventions, including active government involvement in mobilizing and supporting the initiatives. The programs include the PRONAE national school feeding program in Mozambique, the online teacher professional development program in Kenya, teacher training in Niger, back-to-school campaigns in Malawi, basic education training in internally displaced camps in Burkina Faso and Niger, and initiatives addressing sexual and gender-based violence in Mali. The case studies also seek to examine the extent to which the interventions addressed gender, equity, and inclusion. For the Global Partnership for Education (GPE) partner countries, these case studies provide valuable information regarding the operations of education systems and the well-being of learners.

Learning Continuity in Response to Climate Emergencies: Pakistan's 2022 floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Radford, Kate; Kaye, Tom; Perry, Freya (EdTech Hub, 2023)
Building on EdTech Hub's preliminary insights, this extended resource explores Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders in identifying scalable and feasible ways of using EdTech in response to Pakistan’s 2022 floods and improving learning responses in future climate emergencies. We identified these approaches by interviewing flood-affected parents and teachers, government education officers, development partners, local NGOs, and international experts in education in emergencies. We find that during the different phases of response to the emergency, communities’ needs and infrastructural realities keep changing. However, existing responses to support learning have not been able to address these needs at scale. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Technology in education: a case study on Lao People's Democratic Republic - Nietschke, Yung; Dabrowski, Anna (International Education Research, 2023)
This paper was commissioned by the Global Education Monitoring Report as background information for the development of the 2023 Global Education Monitoring (GEM) Report: technology and education, Southeast Asia. Digital technology has the potential to transform learning and offer a solution to persistent challenges in equity of access and quality of learning for all students. COVID-19 has accelerated the adoption of technology to deliver alternative modes of education. It has also put the spotlight on the digital divide that technology creates. This Case Study explores the progress of technology integration in the education sector in Lao PDR in line with its aspirations for a thriving digital economy driven by a digitally-skilled workforce. It explores the current conditions that facilitate or inhibit digitalization of the education sector and considers the impact across the system, sector-wide and school levels. This includes issues relating to digital access, digital literacy of teachers and students, technology infrastructure investments and the regulatory environment. The findings suggest that many of these challenges are not unique to Lao PDR. However, with a clear strategy, political commitment and sustainable resourcing of the education sector, there are opportunities for the Government of Lao PDR and its partners, to set a strong foundation for digitalizing the education system.
Keywords: accepted; checks the GP(disadvntaged group-OOS)T, publisher: Global education Monitering report,; ⛔ No DOI found; ⛔ No INSPIRE recid found

EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Factors Related to Teacher Absenteeism in Sierra Leone: Literature review - Vijil, Alejandra; McBurnie, Chris; Bellinger, Amy; Godwin, Katie; Haßler, Björn (EdTech Hub, 2023)
This report is one of several on the research project on the Impact of GIS-Supported Teacher Allocation in Sierra Leone (Hub-Led Research Programme 3). The education workforce is the most important school-level determinant of student learning. In Sierra Leone, the pupil-to-qualified-teacher ratio rises from 44:1 for schools in urban centres to 76:1 for schools in rural areas. Meanwhile, an average of a quarter of the workforce is absent from school on any given day. This informal literature review provides a summary of the most recent literature on teacher absenteeism, covering a wide range of low- and middle-income countries, including Sierra Leone, where the larger study is being undertaken. For the purposes of this review, we have focused on lessons learnt from sub-Saharan African studies that share similar education contexts and challenges as Sierra Leone. Based on the review, we hypothesise that distance from a teacher’s home to their school and their ability to choose which school they would like to work in impact teacher motivation, school attendance, and time on task. Efficient teacher allocation could improve each of these outcome estimates. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

School-to-School Mobility Patterns and Retention Rates of Payroll Teachers in Sierra Leone - Espinoza-Revollo, Patricia; Ali, Yusuf; Garrod, Oliver; Atherton, Paul; Mackintosh, Alisdair; Ramirez, Ana; Beoku-Betts, Iman; Haßler, Björn (EdTech Hub, 2023)
This report is one of several on the research project on the Impact of GIS-Supported Teacher Allocation in Sierra Leone. Recent studies from this series have shown that being put on the government payroll can incentivise teachers to relocate to remote areas of the country. There is a concern, however, that being put on the payroll does not necessarily ensure the retention of teachers in these areas and that teachers will soon move to locations they consider more favourable. As there is no data on teacher mobility patterns and schools’ teacher retention rates, policies tend to be based on anecdotal evidence. This paper aims to fill this evidence gap by exploring teachers’ school-to-school mobility trends and retention rates using the Annual School Census (ASC) data from 2015 to 2021. Using data on teachers’ individual characteristics, as well as geospatial location data of each school, the paper explores whether mobility patterns vary by teachers’ gender or qualifications and whether the teaching workforce is urbanising. While studies have looked at teacher retention, this study is the first in a low-income country to use school census data to create a panel dataset to study teachers’ movements and school retention rates over time. Keywords: teacher mobility; teacher retention rates; mobility patterns; teacher deployment; Sierra Leone; education An output of the EdTech Hub https://edtechhub.org
Keywords: _r:AddedByZotZen

Using Technology to Improve Education for Marginalised Girls: Lessons in implementation from the Girls’ Education Challenge - Anonymised for Peer Review Purposes (EdTech Hub, 2023)
This article presents the findings of an in-depth study on the implementation of six EdTech-supported projects within the UK Government Foreign, Commonwealth and Development Office (FCDO)’s Girls’ Education Challenge portfolio, which aims to improve education for the world’s most marginalised girls. Using primary key informant interviews and secondary data from sampled projects, the study identifies the core components related to the implementation of EdTech within the sampled projects: evidence-informed design and delivery; building and maintaining relationships across and between stakeholders; comprehensive and continuous training and capacity development; and situating EdTech within a broader holistic model that prioritises gender inclusion to optimise implementation for marginalised girls. In doing so, the study provides key lessons for optimising the future implementation of EdTech for marginalised girls. Keywords: educational technology; girls’ education; programme implementation; Covid-19 An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Exploring the Relationship Between Teachers’ Use of Technology During the Covid-19 Pandemic in India and Their Perspectives on Students’ Motivation to Learn - Tailor, Kavita; Hennessy, Sara; Jordan, Katy (EdTech Hub, 2023)
During the Covid-19 pandemic, a wealth of research emerged to quantify student learning and the accessibility of technology for learners. However, existing evidence highlights that access to technology did not equate to learning, yet few studies have investigated the underlying reasons behind this. As a correlating factor of learning achievement, this report investigates student motivation to learn, as perceived by teachers, and how this may have been influenced by their use of remote technologies during the pandemic. It elucidates the perspectives of teachers working remotely during the pandemic by presenting a secondary data analysis using the world’s largest teacher survey post-Covid-19 (the T4 teacher survey). It complements these findings with qualitative data gathered from eight teachers and education practitioners in India via an online focus group. Results from this study imply that teachers’ pedagogy was more important for student learning motivation than their use of technology and confirmed that more frequent interaction between teachers and students or parents can increase teacher perceptions of student learning motivation. Findings also suggest that student learning motivation may have significantly depended on the continued development of academic and socio-emotional skills. These findings have practical implications for improving remote learning and blended learning environments and for addressing the salient issue of rote learning in India. Keywords: student motivation, technology, learning loss, Covid-19, digital pedagogy, self-determination theory An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Mapping National Digital Learning Platforms - Rui, Tingting; Chuang, Rachel; Thinley, Sangay; AlSheikh Theeb, Thaer; Villavicencio, Xuzel; Rasolohery, Hasiniavo (EdTech Hub, 2023)
This report presents findings from a global mapping exercise of 471 national digital platforms across 184 countries that was conducted by EdTech Hub following a Helpdesk request from UNICEF. The mapping exercise focused on examining three key areas of availability, usability, and inclusivity of national digital learning platforms. The study found that 32% of identified national digital learning platforms no longer exist, have not been updated since 2020, or have links that do not work. Only 30% of platforms offer offline functionality. Eighty-five per cent of platforms were accessible on a basic smartphone. This report serves as a snapshot in time of national digital learning platforms around the world. Future mapping exercises and reports may be carried out to expand on this work. Keywords: platforms, digital, learning, mobile, mapping, offline An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Technology in Education: A Case Study on Timor-Leste - UNESCO Global Education Monitoring Report Team; SEAMEO Regional Centre for Quality Improvement for Teacher and Education Personnel in Science (UNESCO, 2023)

Technology in Education: A Case Study on Viet Nam - Le, Anh Vinh; Luong, Minh Phuong; Do, Duc Lan; Tran, My Ngoc; Bui, Thi Dien (Global Education Monitoring Report Team and Viet Nam National Institute of Educational Sciences, 2023)

Technology in Education: A Case Study on the Philippines - Espinosa, Allen A; Gomez, C Arsenia; Praksis, Miranda A; Adonis, David P; Edna Luz, Abuljon R; Hermosisima, Victoria C; Quinosa Jr, Edwin A; Soliman, Abegail A; De Vera, Jayson L; Claros, Ian Harvey; Cruz, Hardie Gieben; Gonzales, Nepthalie SJ (UNESCO, 2023)
Keywords: ⛔ No INSPIRE recid found

Technology in Education: A case study on Thailand – UNESCO Digital Library - Dipendra, K.C. (2023)
Keywords: ⛔ No INSPIRE recid found

Technology in education: a case study on Lao People's Democratic Republic - Nietschke, Yung; Dabrowski, Anna (2023)

Understanding Teacher School Choice Preferences: What Matters Most for Teacher Deployment in Sierra Leone? (EdTech Hub Preprint, 2023)
This exploratory mixed-methods study investigates the factors that shape where teachers want to work in Sierra Leone. We identify five dominant factors: monetary incentives, school conditions, opportunities for professional development and support, school location, and relationships with the school and the community. Importantly, these factors combine to push and pull teachers to different locations. Moreover, the factors interact with individual teacher characteristics such as gender, family status, and experience to influence school choice preferences. This set of factors — and their interaction with certain teacher characteristics — continues to shape preferences as teachers move up the career ladder. Keywords: Teacher deployment, teacher preferences, Sierra Leone, teacher supply, remote schools An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Sierra Leone Case Study: Review of Technology-Based Interventions to Address Child Marriage and Female Genital Mutilation - Data-Pop Alliance; United Nations Population Fund; UNICEF (2023)

The Future of EMIS: A Public Financial Management Perspective - Cresswell, Simon; Long, Cathal; Fraser, Alasdair (EdTech Hub, 2023)
Policymakers in low- and lower-middle-income countries are in a bind: while more complex EMIS designs may make processes more likely to fail following donor exit, simple EMIS designs do not provide enough information to track the effects of reforms and progress addressing the learning crisis. Even for basic measures, EMIS appear to generate inaccurate data in many cases. Reflections on EMIS implementation challenges point to demand and supply issues, with the former being the more important determinant for realising EMIS potential and their ongoing development. This paper considers demand and supply for EMIS from a public financial management (PFM) perspective. Keywords: public financial management, budgeting, digital, data governance, education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Raising Readers: Can mobile technology enable Kenyan schools to improve parent and carer engagement in reading with their children? - Nicolai, Susan; Khan, Amina; Kartha, Ashwati; Bapna, Akanksha; Kamninga, Tony (EdTech Hub, 2023)
Deploying design-based, mixed-methods research, the study Raising Readers (Phase 1) explores how technology can be best used to strengthen parent and carer engagement with children’s reading in Kenya. In close collaboration with Worldreader, a digital reading organisation, five co-designed modalities (parental training, feedback loops, nudges/messaging, incentives, and reading celebrations) were tested in 14 schools across Nairobi and Kiambu counties over 12 weeks in 2022. The intervention helped to assess the potential of the different modalities in facilitating parental/carer engagement around children’s reading using the BookSmart app. As measured by average reading time, intervention groups showed higher engagement using BookSmart than the control group. ‘Incentives’ led with 39 hours 29 minutes average reading time per school over 12 weeks, followed by ‘reading celebrations’ with 24 hours 13 minutes. ‘Feedback loops’ and ‘training’ had comparable levels (10 hours, 28 minutes, and 9 hours, 27 minutes per school, respectively). ‘Messaging / nudges’ had the lowest engagement (5 hours 57 minutes versus 3 hours 2 minutes in the control group). Parental/carer knowledge, attitudes, and practices supporting their child's reading improved with the interventions. Findings of Phase 1 were used to inform the design of Phase 2. Keywords: Education, app, reading, school, child, Kenya An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Outputs Register: The Impact of GIS-Supported Teacher Allocation in Sierra Leone - Haßler, Björn; McBurnie, Chris; Beoku-Betts, Iman; Frazer, Madleen Madina (EdTech Hub, 2023)
EdTech Hub, Fab Inc, and the Education Workforce Initiative have produced the outputs listed in this document as part of the EdTech Hub-commissioned research project on ‘GIS-supported teacher allocation in Sierra Leone’. This research project began in January 2022. This document lists all outputs produced under this project. All outputs are available to the public via the EdTech Hub Evidence Library. An output of the EdTech Hub, https://edtechhub.org
Keywords: Author:OpenDevEd; HLR3; _C:Sierra Leone SLE; _r:AddedByZotZen

Teacher Deployment in Sierra Leone: Lessons learnt and going forward - Beoku-Betts, Iman (EdTech Hub, 2023)
This report provides an overview of the teacher deployment process in Sierra Leone prior to and including 2022. Through interviews with key stakeholders in the Ministry of Basic and Senior Secondary Education (MBSSE) and the Teaching Service Commission (TSC), we look at lessons learnt from the deployment process and next steps for how teacher deployment can be implemented. Although there are a number of volunteer teachers in Sierra Leone, the TSC are aiming to increase the number of qualified teachers on the government payroll as well as retaining teachers in rural areas. It was noted that teachers from rural areas being put on the government payroll and deployed to rural schools are better placed to teach in rural schools than teachers moving from urban to rural areas. Hpwever, it is still challenging to find qualified teachers in these rural areas. The TSC want to look at how they can target teachers to take up rural positions, either through distance learning to gain the right qualifications or working with teacher training institutions (TTIs) to prioritise schools in rural areas for placement. Overall, the TSC want to use data as the basis for decision-making on deploying teachers equitably. Keywords Teacher deployment; teacher training; unqualified teachers; volunteer teachers; rural schools; data for decision-making An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Teacher Retention and Mobility in Sierra Leone: What factors motivate teachers to stay at or leave schools? - Lurvink, Anne-Fleur; Mansaray, Kabiru; Kamara, Josephine; Khanu, Alimamy James; Cameron, Emma; Godwin, Katie; Haßler, Björn (EdTech Hub, 2023)
The current study is the third in a series of research studies, which aim to generate evidence that can support the MBSSE and TSC with their teacher allocation and deployment strategy. Our first study investigated teacher preferences for school choice and uncovered important considerations for teacher deployment. Following this, we investigated mobility patterns for teachers who are on the government payroll, and payroll teacher retention rates. The latter study helped us understand where teachers move to when they change schools, and also helped us identify areas with high (hot spots) and low retention rates (cold spots). The current study is explanatory in nature and aims to understand why teachers stay at or leave their schools. Keyword: teacher allocation; teacher retention; teacher mobility; Sierra Leone An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Digital literacy through Let’s Read app to improve the reading interest of elementary school students - Samsudin, Dea Fariska Ardiana; Rahmawati, Fitri Puji (International Conference on Learning and Advanced Education (ICOLAE 2022), 2023)
This study aimed to determined digital literacy through Let's Read application (app) as an innovation to increase students’ reading interest and to find out the results of using the let's read app in reading activities in elementary schools. The method used in this study was descriptive qualitative with a case study design. The authors collected...

Use of Assistive Education Technologies to Support Children with Visual and Hearing Difficulties in the East Asia and Pacific Region - Yarrow, Noah; Pynnonen, Lauri; Song, Chuyu; Bhardwaj, Riaz; Spiezio, Mario (World Bank, 2023)
Evidence on the uptake, use, and impact of EdTech at scale on participation and learning among students with disabilities in low- and middle-income countries remains very limited. This report presents findings on access to EdTech for children with difficulties in hearing and vision in middle-income countries (MICs) in the East Asia and Pacific (EAP) region using three approaches: (i) a systematic regional literature review; (ii) interviews with 17 actors from the education technology private sector across the EAP region; and (iii) case studies from four countries: Vietnam, the Philippines, China, and Tonga. The main findings from the literature review are that most EdTech solutions in EAP MICs were applied at very small scale, with a focus on the tech testing stage, and only two of the 13 identified studies from a sample of 1,661 studies measured changes in student learning outcomes. The private sector interviews indicate qualitatively that most actors in this space are unaware of the needs of children with vision and hearing disabilities, and that other challenges such as profitability and general inequalities related to access to devices and high-speed internet receive the most attention. The case studies report no examples of national deployment of any assistive education technology, though there are multiple examples of small-scale digital approaches developed by individual schools or NGOs and shared locally or, in two cases, regionally. In looking at country contexts for the case studies, we found a lack of publicly available data on spending for assistive EdTech in EAP, a lack of data on (a) prevalence of disabilities among the student population, (b) student learning, and (c) student persistence in higher grades. We examine new data on policy-maker estimates of access and inclusion of children with disabilities, and find that despite support for inclusion, there is large scope for improving data collection, service delivery and access to assistive EdTech in MICs in the EAP region.

Educational loss at times of crisis: the role of games in students’ learning in Palestine and Iraq - Ali, Kareema; Burgos, Daniel; Affouneh, Saida (Sustainability, 2023)
This study examines the role of educational games in compensating for educational loss and their impact on students’ motivation towards learning during crises in Palestine and Iraq. Additionally, the study considers the challenges facing the employment of this strategy and ways to overcome these challenges. By performing separate open semi-structured interviews with a group of 10 educators from university professors, teachers, and educational supervisors, the study used the qualitative descriptive approach which designs multiple case studies. The results showed the prominent role that educational games play in increasing students’ motivation towards learning and compensating for educational loss through what they add to the fun and suspense in the learning process and how they shorten time and effort and help students to engage and cooperate in acquiring knowledge, skills, and values. The results also reveal common challenges that face the employment of educational games. These challenges are social, economic, technological, challenges related to school environment, and psychological challenges. The study shows the possibility of overcoming these challenges by providing funding sources, preparing plans to employ educational games, and developing teachers’ capabilities to implement them in their teaching practices.
Keywords: crises; educational games; educational loss; motivation

Randomised Controlled Trial Protocol: Digital personalised learning to improve literacy and numeracy outcomes in Kenyan classrooms - Major, Louis; Daltry, Rebecca; Otieno, Mary; Otieno, Kevin; Zhao, Annette; Hinks, Jessica; Sun, Chen; Friedburg, Aidan (EdTech Hub, 2023)
This protocol provides a detailed overview of a cluster-randomised controlled trial (RCT) being undertaken in pre-primary schools in Kenya. The RCT seeks to rigorously investigate the impact of a classroom-integrated digital personalised learning (DPL) tool on early grade numeracy and literacy learning outcomes. The protocol is being disseminated prior to endline data analysis to promote transparency and a comprehensive understanding of the RCT approach and design. This protocol was originally published in October 2023. This is an updated version where we have a) clarified that the sample size stated in Sections 2 and 2.2 is the 'pre-attrition' sample; and b) added a paragraph to Section 2.4.1 to provide further clarification regarding the use of code-switching. No changes to the analytical approach have been made. Keywords: digital personalised learning; DPL; Randomised controlled trial; RCT; research methodology; learning outcomes; Kenya An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Teacher Continuous Professional Development in Tanzania: Lessons Learnt - Chachage, Kristeen; Thakrar, Jay (EdTech Hub, 2023)
This report shares the experience and learning from the activities carried out as part of the Government of Tanzania's efforts to operationalise its National Framework for Teacher Continuous Professional Development (TCPD), which shifts TCPD from discreet workshops to cost-effective, ongoing, school-based professional development. It is among the first of its kind at a national level, particularly in low- and middle-income country contexts. Through a collaborative and responsive approach of adaptive technical assistance and innovation, the EdTech Hub team supported Government of Tanzania partners in developing and implementing a technology-enhanced, school-based, national TCPD system. This report begins with an overview of the activities implemented and then consolidates reflection through nine lessons learnt that could help inform current and future thinking on the design, delivery, and funding of TCPD programming in Tanzania. The TCPD reflected in this report is specific to Tanzania's teaching and learning environment. While we recognise that environments can vary widely, even between countries with similar goals and objectives, the report also seeks to contribute to any current and future analyses that collate features of effective TCPD from around the world. Keywords: teacher professional development; teacher training; technology; learning management system; communities of learning; teacher needs assessment; An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Human-AI collaboration to identify literature for evidence synthesis - Spillias, Scott; Tuohy, Paris; Andreotta, Matthew; Annand-Jones, Ruby; Boschetti, Fabio; Cvitanovic, Christopher; Duggan, Joe; Fulton, Elizabeth; Karcher, Denis; Paris, Cecile (2023)
Systematic approaches to evidence synthesis can improve the rigour, transparency, and replicability of a traditional literature review. However, these systematic approaches are time and resource intensive. We evaluate the ability of OpenAI’s ChatGPT to undertake two initial stages of evidence syntheses (searching peer-reviewed literature and screening for relevance) and develop a novel collaborative framework to leverage the best of both human and AI intelligence. Using a scoping review of community-based sheries management as a case study, we nd that with substantial prompting, the AI can provide critical insight into the construction and content of a search string. Thereafter, we evaluate ve strategies for synthesising AI output to screen articles based on prede ned inclusion criteria. We nd low omission rates (< 1%) of relevant literature by the AI are achievable, which is comparable to that of human screeners. These ndings show that generalised AI tools can assist reviewers with evidence synthesis to accelerate the implementation and improve the reliability of a review.
Keywords: _Added-ailr-2024

Investing in disaster preparedness and effective recovery of school physical infrastructure - Opabola, Eyitayo A.; Galasso, Carmine; Rossetto, Tiziana; Meilianda, Ella; Idris, Yunita; Nurdin, Sukiman (International Journal of Disaster Risk Reduction, 2023)
The importance of functioning education infrastructure for the post-disaster recovery of communities is well-acknowledged. Yet, recent natural-hazard events worldwide have highlighted that school facilities still face many post-disaster recovery-impeding challenges. A significant investment in resilience enhancement through appropriate disaster preparedness and post-disaster recovery management is needed to tackle such global challenges. This paper summarises a series of stakeholder engagements (through interviews and focus group discussions) aimed at providing evidence-based recommendations to foster a more rapid and effective post-disaster recovery of school physical infrastructure in disaster-prone marginalised communities. The case-study community is in Central Sulawesi, Indonesia – a region still recovering from the 2018 Central Sulawesi earthquake, tsunami, and liquefaction, which caused damage to over 1200 schools. The considered stakeholders have significant experience in post-disaster recovery management in Central Sulawesi. This paper identifies early-response funding mechanisms, genuine collaborations between stakeholders, and improved capacity for self-organisation as critical elements for an inclusive, sustainable, safer, and more resilient school physical infrastructure. Although the discussion in this paper focuses on Central Sulawesi, the project's outcomes are scalable to other regions in Indonesia, South-East Asia, and other disaster-prone developing nations.
Keywords: Disaster risk reduction; Preparedness; Resilient recovery; School physical infrastructure; Stakeholder engagement

Testing EdTech Interventions in Bandarban: Key Findings from the EdTech Hub Sandbox - Tanweer, Rabia; Plaut, Daniel; Datta, Rupa; Nashtaran, Trishia; Rahman, Asad; Ahmed, Shakil; Fazly, BMRabbi; Hoque, Rashedul; Moon, NurunNahar; Afroze, Sadia (EdTech Hub, 2023)
The Covid-19 pandemic has catalysed the need for technology-enhanced education globally. This is no different in Bangladesh, where the Education Section of the UNICEF Bangladesh Country Office is seeking a better understanding of the role and potential of EdTech to improve numeracy skills among the most marginalised learners. In efforts to do this, UNICEF Bangladesh partnered with EdTech Hub to in which EdTech interventions contribute the most to numeracy learning for marginalised learners in Bangladesh. This was explored through a sandbox in Bandarban, a remote region in South-Eastern Bangladesh. This report synthesises the evidence generated from this EdTech Hub sandbox. While further research is needed, its findings suggest that multimedia classrooms, which were found to be present and functioning in most schools in the region, are a promising intervention. Their effectiveness and implementation are worthwhile avenues for further research. Keywords: Bangladesh, Low connectivity/electricity, rural, marginalised learners, blended learning, tablets An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

High-quality education for better sustainability and resiliency - Prazian, Michael V; Prykhodko, Viktoria M (IOP Conference Series: Earth and Environmental Science, 2023)
The world meets poly crises in climate, pandemic, energy, food, human rights, and migration; hot and cold wars have come in Europe and other regions. The scope of the tasks becomes unprecedented, and their complexity demands high-level skill sets and teaching culture. Education moves into epicentres of the fight for better sustainability and resilience. The United National Sustainable Development Goals Four (SDG4) supposes allocating and diligently using several trillion US dollars for the next decades. The ambitious goals drive the educational system to be at a decent level regarding outcome and process. Saving gratitude to functions of a fundamental human right, a public good, gender equality, and an absolute right to education for all, the author urges that high-quality education is the priority because it will help society to cope with a new level of challenges and even existential threats the climate-like. The article describes the methodology and the importance of soft-hard skills for teaching and learning. The secondary-based sources research illustrates practical results regarding the educational process. The Triple Bottom Line principle (Planet, Profit, People) encompasses many disciplines engaging the main aspects of sustainability and resiliency and climate change for the university curricula in a coherent way. The article considers future trends in high education and case studies connected with the European Green Deal, environmental, social, and governance (ESG) reporting and practical aspects of Green Growth and De-Growth Theory. The Quality of Education reflects the regulator’s requirements and social and personal expectations. Life-long learning becomes a norm. The authors consider university products, processes and platforms through the lens of future trends, threats and opportunities. In times of turbulence, the results obtained through students’ upskilling and reskilling programs should fit the demands of new jobs, technologies, and financial mechanisms.

The Use of Technology to Promote Equity and Inclusion in Education in North and Northeast Kenya - Otieno, Jennifer; Kaye, Tom; Mbugua, Wanjiku (EdTech Hub, 2023)
Kenya has been lauded as having one of the most progressive and effective education systems in Africa. Significant investments in education funding, innovative technology-enabled approaches to improve teaching and learning, and committed leadership make Kenya an example for neighbours and others across the world. However, at a sub-national level, significant variances in education access and quality arise. While many improvements have been made to participation, quality, equity, and inclusion in education in Kenya, there are persistent disparities in access and outcomes for rural learners, girls, learners with disabilities, and other vulnerable populations. The North and Northeastern (N/NE) counties of Kenya are where some of the greatest disparities exist. Our research examines the context of N/NE Kenya to understand why these disparities exist, and how technology can play a role in increasing equity and inclusion in education in the region. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech to Support Out-of-School Children and Adolescents - Thinley, Sangay; Rui, Yang (EdTech Hub, 2023)
This Helpdesk report was created in response to a request from the World Bank Malawi Education Team for a curated list of resources on examples of EdTech interventions targeting out-of-school children and adolescents to inform an ASA (Advisory Services and Analytics) output. The ASA output will provide policy options to improve second-chance learning and foundational skills for out-of-school children (OOSC). To provide the World Bank Malawi team with adequate information on the above. This curated list begins with an introduction to the use of EdTech to support out-of-school children and youth, and then moves on to present examples of such interventions and programmes within Malawi, as well the wider African region and the rest of the world. This list is designed to serve as a resource for the team and does not make any direct recommendations on actions to be taken. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found